Pengaruh Harga, Iklan, Dan Kualitas Produk Terhadap Keputusan Pembeliaan Kartu Seluler Indosat Mentari Studi Kasus Pada Universitas Muhammadiyah Surakarta - Nugroho, Roman; , Drs. Sujadi, M.M (2015)
The aim of this study was to determine the influence of advertising, pricing, and product quality on purchasing decisions. The population in this study is a university student surakarta especially in economics and business. The sample in this study was 100 people who have and are using a mobile card indosat sun, with the division of 50 faculty of economics, faculty of informatics engineering 30, and 20 students of the faculty of engineering. By gathering data using questionnaires. Results of multiple regression analysis, namely, Y = 0.240X1 + 0.292X2 + 0.392X3 most influential independent variable is the variable quality of the product (0.392), then the variable price (0.292) and the last variable ad (0240). T test results prove that all the independent variables (advertising, pricing, and product quality) has positive influence on the dependent variable is kuputusan purchase mobile Katu indosat sun. That is according to the consumer that the three independent variables are considered important when buying a cellular card indosat sun and the coefficient of determination (adjusted R2) were obtained for 0,806. This means that 80.6% purchase decision is influenced by advertising, price, and quality of products while the remaining 19.4% is influenced oelh other variables that are not researched in this study. Keywords : Influence of advertising, pricing, and product quality on purchasing decisions